Re- Socialization of Probationers in West Bengal: The need of Sociological Re-integration of Ex-Probationers - Shah, Asif Iqubal; Chakraborty, Nirmal Kanti; Bhattacharya, Bhupal (International Journal of Psychosocial Rehabilitation, 2020)
Over the years after the gradual development of modern criminological thinking, probation evolved as a viable means of reformation and also an alternative to incarceration. Probation is such a system which acts as a bridge to fill the so-called gap created between the harsh realities of our Penal Code and the modern trend in penology directed to humanize the criminal laws. It is believed that if a man deviates from the path of rectitude, he can be directed to the right path through proper assistance and guidance. If an offender commits an offence it may be because of necessity, inadvertence or being in association with bad characters or just to wreck vengeance. Probation deals with such first-time offenders under conditional suspension of their sentence after being convicted and they are placed under the supervision of a probation officer subject to certain conditions solely with a view to reestablish and rehabilitate them in the society. The author in the present paper has tried to highlight how far the Probation system proved to be a success in re-socializing the probationers into the mainstream of the society by undertaking an empirical study of the ex-probationers of West Bengal.